Transformation of Teacher Strategy in Classroom Management to Enhance Islamic Cultural History Learning - Euis Ismayati Yuniar; Trikawati Trikawati; Taufik Imron; Nurjaman Nurjaman; Lia Nurliana (Institut Muslim Cendekia, 2026)
Classroom management is a crucial factor in enhancing learning effectiveness and creating a conducive learning environment, particularly in the subject with SKI. This study is important because effective classroom management can increase student engagement and achievement; however, its practice still varies among teachers. The objective of this study is to describe the strategies of teachers in managing the classroom during SKI learning in Class XII Social 3 at State Islamic Senior High School 1 Serang. This study employed a descriptive qualitative approach with a field study design, and data were collected through observation, questionnaires, and documentation. The results indicate that the teacher implements classroom management strategies that encompass the physical classroom arrangement, student behavior management, the use of learning media, active student engagement, a communicative personal approach, and collaborative seating arrangements. These strategies enhance student participation, discipline, and learning comfort. The novelty of this study lies in its practical presentation of classroom management strategies based on social interaction in SKI subjects that can serve as a reference, with implications for improving the quality of learning in Madrasah Aliyah.